Functional electrical stimulation (FES) in adults with neurological disorders and foot drop: orthotic and therapeutic effects in short- and long-term users - Bleichner, Niklas; Alimusaj, Merkur; Heitzmann, Daniel W. W.; Stähle, Andreas; Weichold, Claudia; Putz, Cornelia; Flor, Herta; Nees, Frauke; Wolf, Sebastian I. (Bioengineering, 2026)
Functional electrical stimulation (FES) is widely used to improve gait in individuals with neurological impairments; however, early responses in adults with congenital conditions, such as cerebral palsy, who are newly exposed to FES, remain poorly understood. This study investigated the orthotic and therapeutic effects of FES in short- and long-term users using standardized three-dimensional gait analysis. In this longitudinal study, short-term users (G1; n = 13; mean age 31.7 ± 18.1 years) were evaluated both without and with FES and followed over a 4–12-week insurance-covered trial period. Long-term users (G2; n = 11; mean age 32.2 ± 11.0 years), who had used FES for at least one year, were reassessed over a standardized 12-week interval. Linear mixed-effects models assessed the effects of FES and time, with subjects included as random effects to account for inter-individual variability. G1 showed significant therapeutic adaptations, including increased walking speed and step length and reduced step width, accompanied by decreased dorsiflexion during stance and swing, while no significant orthotic effects were observed. G2 demonstrated clear orthotic responses, such as increased dorsiflexion at heel strike and during swing and improved walking speed and step length, with minimal evidence of additional therapeutic adaptation. The initial reduction in dorsiflexion in G1 warrants further investigation. These findings suggest that evaluation timelines may need to be extended and that outcome measures beyond foot clearance should be considered, particularly given the heterogeneity and severity of congenital neurological conditions.
Gesehen am 26.02.2026